Perspektif Viktimologi terhadap Fenomena Victim Blaming pada Anak dalam Konflik Keluarga - Sulis Nurlaila; Nicolo de’Albergati; Muhammad Rifki Nurrasman; Hana Faridah (Pusat Riset dan Inovasi Nasional, 2025)
The phenomenon of victim blaming remains a serious issue in various cases of violence, including family conflicts. Children who experience physical, psychological, or neglect-related abuse often face not only violence but also social stigma that blames them for their circumstances. From a victimology perspective, victim blaming against children in family conflicts occurs due to factors such as patriarchal culture, power imbalances within the family, and a lack of legal awareness regarding children's rights. This study employs a normative juridical method with a qualitative approach to examine the phenomenon of victim blaming against children in family conflicts based on victimology theory. The findings reveal that victim blaming in family conflicts manifests in various forms, including justification of violence against children, minimization of the harm caused, and denial of the perpetrator's role. The psychological and social impacts of this phenomenon are extensive, leading to anxiety, depression, post-traumatic stress disorder (PTSD), and difficulties in forming healthy social relationships. To address this issue, active involvement from families, educational institutions, and child protection organizations is crucial in providing education and advocacy for children's rights. Additionally, victimology perspectives can be utilized to develop policies that support victims, prevent the recurrence of family violence, and minimize the practice of victim blaming against children.